Communication in the Implementation of Electronic Justice Policy in the Mempawah Religious Court - Hardilina; Elga Yulindisti; Arifin (International Journal of Science and Society, 2023)
Electronic justice (e-court) is a justice system that is implemented electronically to provide easy services for court officials and parties litigating in court through the use of information technology. Application of electronic court to answer 3 (three) main problems: delays, accessibility, and integrity. The use of e-court can prevent interactions between parties related to court officials, thereby minimizing the occurrence of ethical deviations or legal violations. Apart from that, it can also reduce time, energy, and costs so that the process is more effective and efficient. The aim of the research is to find out and analyze the factors that influence the implementation of electronic court policies at the Mempawah Religious Court using George Edward III's theory (communication, resources, disposition, and bureaucratic structure). The research method used is descriptive-qualitative. The data sources were taken from documents and interviews with related parties. The research results show that electronic courts have not been utilized by people seeking justice due to several factors, including: people do not know about electronic courts, are technologically illiterate, do not have the means to use electronic courts, do not understand electronic court mechanisms, and have internet network problems. Future projections for electronic courts to be optimally utilized by people seeking justice require massive outreach and the availability of adequate equipment.